Gereja di Ruang Publik Indonesia Berdasarkan Pemikiran A.A. Yewangoe - Sinuraya, Alosius Des Afriando (DUNAMIS: Jurnal Teologi dan Pendidikan Kristiani, 2025)
Abstract. A.A. Yewangoe through his thoughts can be said to be a theo-nationalist figure because of his ability to integrate Christian teachings with the socio-cultural context of Indonesia in an effort to build a just and dignified democratic society. In this regard, this study focuses on Yewangoe's intellectual, theological, and ecclesiological analysis in responding to social, political, and democratic issues in Indonesia. Emphasis is placed on how Yewangoe integrates Christian teachings with Indonesian socio-cultural values to create a democratic society. Yewangoe emphasizes that the church has an active role in creating a just social order, by combining Christian values and local wisdom of Indonesian society. This idea encourages the church and Christians to be more reflective about their responsibilities in the public sphere, while at the same time criticizing the view that separates the church from social life. Thus, Yewangoe’s thoughts offer a significant perspective on the role of the church in the formation of a more just and dignified Indonesian society.Abstrak. A.A. Yewangoe melalui pemikirannya dapat dikatakan sebagai tokoh teo-nasionalisme karena kemampuannya mengintegrasikan ajaran Kristen dengan konteks sosio-kultural Indonesia dalam upaya membangun masyarakat demokratis yang adil dan bermartabat. Sehubungan dengan ini, penelitian ini berfokus pada analisis intelektual, teologis, dan eklesiologis Yewangoe dalam merespons isu-isu sosial, politik, dan demokrasi di Indonesia. Penekanan diberikan pada bagaimana Yewangoe mengintegrasikan ajaran Kristen dengan nilai-nilai sosio-kultural Indonesia untuk menciptakan masyarakat demokratis. Yewangoe menegaskan bahwa gereja memiliki peran aktif dalam menciptakan tatanan sosial yang berkeadilan, dengan memadukan nilai-nilai Kristiani dan kearifan lokal masyarakat Indonesia. Gagasan ini mendorong gereja dan umat Kristen untuk lebih reflektif terhadap tanggung jawab mereka di ruang publik, sekaligus mengritisi pandangan yang memisahkan gereja dari kehidupan sosial. Dengan demikian, pemikiran Yewangoe menawarkan perspektif yang signifikan bagi peran gereja dalam pembentukan masyarakat Indonesia yang lebih adil dan bermartabat.